PERFORMANCE LEGITIMACY: THE SOCIO-ECONOMIC CONDITIONS UNDER THE SULTAN’S ADMINISTRATION IN YOGYAKARTA - Dwi Harsono (NATAPRAJA, 2020)
In his capacity as governor, Hamengkubuwono has a coordinating role to play between the provincial, municipal and district governments in Yogyakarta. Though most policy responsibility lies with the districts and city of Yogyakarta, the sultan still has an important function to fulfil as effective cooperation between different tiers of government is a crucial factor in facilitating successful policy outcomes at the local level. For the sultan, his role as mediator and coordinator works well because it reinforces public perceptions of him as a neutral arbiter who stays aloof from the bickering of day-to-day politics. Over the years, he has cultivated this image of a paternalistic figure by making regular appeals to district heads and the mayor of Yogyakarta to serve the people better. In the rare events where conflicts arise over public policy (for example over land), Hamengkubuwono successfully deflected the blame for controversial policies to the lower-level governments, even though the royal palace often has a direct stake in these policy decisions.